Analysis of the Fracture Failure of ST90 Coiled Tubing - Gao, Runqiu; Duan, Jianliang; Dong, Jian (International Journal of Computer Science and Information Technology, 2025)
This article determines the causes of fracture failure of the ST90 coiled tubing through chemical composition analysis, dimensional measurement, metallographic analysis, and hardness testing of the fractured tubing sample. The material test results show that the chemical composition, size, grain size and hardness test results of the fractured coiled tubing meet the standard requirements, and no abnormal results are found. There is mechanical trauma in the fracture and suspected improper operation on both sides of the fracture position, which causes the tube body damage by the stacking of the clamping blocks, that will cause the deformation of the coiled tubing. The thinning of the wall thickness and the increase of hardness will reduce the strength of the tubing, which is the main reason for the fracture of the coiled tubing.